EL DESEMPEÑO PROFESIONAL DE LOS (AS) DOCENTES DE LA ESCUELA FISCAL ''LAURA CARBO'' DE LA CIUDAD DE VENTANAS Y SU INCIDENCIA EN EL LOGRO DE APRENDIZAJES SIGNIFICATIVOS DE SUS ESTUDIANTES, DURANTE EL PERIODO LECTIVO 2012-2013. - LEONOR EMILIA ARAGUNDI RAMIREZ (2013)
THE PROFESSIONAL PERFORMANCE OF THE TEACHERS OF THE ''LAURA CARBO'' TAX SCHOOL OF THE CITY OF VENTANAS AND ITS IMPACT ON THE ACHIEVEMENT OF SIGNIFICANT LEARNING OF THEIR STUDENTS, DURING THE 2012-2013 SCHOOL PERIOD.